PENANGANAN ANAK TUNAWICARA : STUDI KASUS - Dewi Nur Aysyah; Henny Dwi Yanti; Wahyuni Emilia Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Inclusive education should place children with special needs on an equal footing with other normal children. Speech impairment or speech disorder is a condition in which a person is unable to express his ideas to others by using his speech apparatus. This type of research is a case study so it uses a qualitative approach. The location of this research was conducted at SLB Negeri 1 Bengkulu City, Langsa City. The subject of this study was a mute child who was also a teacher at SLB Negeri 1 Bengkulu City, Langsa City. In collecting data in this study using interviews, observation and also documentation. Also in this study, the authors are interested in examining every handling of speech-impaired children at RA Al-Ashriyah, Langsa City. The order of each problem to be studied is: What are the characteristics of speech-impaired children at SLB Negeri 1 Bengkulu City, Langsa City? How are mute children handled at SLB Negeri 1 Bengkulu City, Langsa City? and What obstacles do teachers face in dealing with mute children at SLB Negeri 1 Bengkulu City, Langsa City? Something that has always been a question about the handling carried out by teachers in schools.